The Role of Customer Trust as a Mediator in Building Loyalty to Agung Toyota After-Sales Service - Rahmadani Hidayat; Sarjon Defit; Yulasmi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the role of customer trust as a mediator in building loyalty in Agung Toyota's after-sales service. Customer loyalty is an important aspect of business sustainability and service quality is considered a factor that influences it. However, in practice, the effect of service quality on customer loyalty is not always direct, but can be mediated by customer trust factors. This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to 200 respondents who are Agung Toyota Pekanbaru Harapan Raya customers. The data analysis technique used is Structural Equation Modeling (SEM) with the help of SmartPLS software. The results of the study indicate that service quality has a positive and significant effect on customer trust. Furthermore, customer trust is proven to have a positive and significant effect on customer loyalty. Interestingly, service quality also has a direct effect on customer loyalty, but the effect becomes stronger when mediated by customer trust. This indicates that trust acts as a partial intervening variable in the relationship between service quality and customer loyalty. The implications of this study indicate that companies need to consistently improve the dimensions of service quality to build customer trust, which will ultimately increase their loyalty. By focusing on creating trust through superior service, companies can build long-term, profitable relationships with customers.